Involvement of cytosolic phospholipase A2α in MMP-9 Up-regulation - P. Montreekachon (2018)
Matrix metalloproteinase-9 (MMP-9) is important in the pathogenesis of periodontitis. Cytosolic phospholipase A22α (cPLA22α) is involved in MMP-9 up-regulation in human monocytes. We tested the hypothesis that cPLA22α also regulates MMP-9 induction by Fusobacterium nucleatum and by phorbol 12-myristate-13-acetate (PMA) in gingival epithelial cells. While PMA induced MMP-9 expression considerably, F. nucleatum did so moderately. This time-course study demonstrated that MMP-9 mRNA up-regulation occurred at 3 hours, whereas MMP-9 secretion and activity in cell-free supernatants occurred at 12 hours. cPLA2α mRNA was constitutively expressed in gingival epithelial cells. Transient activation of cPLA2by Ser505 phosphorylation was observed in the nuclei upon stimulation, suggesting its role as a transcription factor, while cPLA2protein expression remained unchanged. Induction of MMP-9 expression and activity was significantly inhibited by 1 1/4M of the specific cPLA2α inhibitor (P < 0.01). These findings demonstrate the involvement of cPLA2α in MMP-9 up-regulation.